2012
DOI: 10.1007/s10853-012-6462-7
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of silver nanoparticles on silk fabric with PNP for antibacterial finishing

Abstract: This research presents a generic strategy to fabricate antibacterial textile through in situ synthesis of silver nanoparticles on the fabric with smart polymeric molecules. Silk fabric and polyamide network polymer (PNP) were chosen for this study. PNP which has numerous amino groups and three-dimensional structure was applied to entrap silver ions into silk fabric. The pretreated silk fabrics were heated by steam method to make silver nanoparticles synthesized in situ on them without any other reductant and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Comprehensive investigations of functionalised textiles in the scientific literature have shown that textiles can be functionalised with well-defined NPs under laboratory conditions (Zhang et al, 2012;Nguyen Khanh et al, 2013). However, it is reasonable to assume that upscaling of functionalization methodologies to the industrial level may result in different outcomes from those achievable under well-controlled laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive investigations of functionalised textiles in the scientific literature have shown that textiles can be functionalised with well-defined NPs under laboratory conditions (Zhang et al, 2012;Nguyen Khanh et al, 2013). However, it is reasonable to assume that upscaling of functionalization methodologies to the industrial level may result in different outcomes from those achievable under well-controlled laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…PNP was prepared as described in our previous paper [20]. Woven, bleached, and scoured cotton fabric (58×30 number of yarns per cm 2 , 120 g·m -2 ) was obtained from the Huafang Group (China).…”
Section: Methodsmentioning
confidence: 99%
“…During heating process, the formed will transform into ZnO nuclei and generate ZnO NPs with the as growth unit [24]. Due to the special structure of PNP, which has interior sealed-in polymeric nanocages [20], it can confine the growth of ZnO NPs and protect them. Therefore, the size of ZnO NPs could be controlled and the prepared ZnO NPs/PNP hybrid exhibited good stability in aqueous solution.…”
Section: Synthesis Of Zno Nps In Aqueous Solution By Pnpmentioning
confidence: 99%
See 1 more Smart Citation
“…AHSAN HABIB 1,4 , MST. ZAKIA SULTANA 1,5 and HUI-HONG LIU been withdrawn to modify surface of cellulose and protein fibers by incorporating metal and metal assisted nanoparticles (NPs) due to perform some multifunctional attributes such as antibacterial, UV protection, antistatic and self-cleaning [5,6]. Among the metallic nanoparticles, AgNP has nanosize between 1 nm and 100 nm and consider one of the best candidates for several applications including biosensing, microbial activities, drug delivery, catalysis, electrochemical, conductivity, etc.…”
Section: Introductionmentioning
confidence: 99%